2009
DOI: 10.1111/j.1469-8137.2009.03026.x
|View full text |Cite
|
Sign up to set email alerts
|

A relationship between galactic cosmic radiation and tree rings

Abstract: Summary• Here, we investigated the interannual variation in the growth rings formed by Sitka spruce (Picea sitchensis) trees in northern Britain (55°N, 3°W) over the period in an attempt to disentangle the influence of atmospheric variables acting at different times of year.• Annual growth rings, measured along the north radius of freshly cut (frozen) tree discs and climatological data recorded at an adjacent site were used in the study. Correlations were based on Pearson product-moment correlation coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 53 publications
1
24
0
2
Order By: Relevance
“…For example, Dengel et al (2009) have recently published a small but significant correlation between cosmic ray fluxes and tree growth rates in the UK. On its own, one such correlation means little for climate studies, but in the context that most paleoclimate evidence for solar influences of climate involves reported correlations between cosmogenic isotopes and proxies for local and regional rainfall rates (see review by Lockwood & Fröhlich 2007), they may take on additional significance.…”
Section: Direct Gcr Effectsmentioning
confidence: 99%
“…For example, Dengel et al (2009) have recently published a small but significant correlation between cosmic ray fluxes and tree growth rates in the UK. On its own, one such correlation means little for climate studies, but in the context that most paleoclimate evidence for solar influences of climate involves reported correlations between cosmogenic isotopes and proxies for local and regional rainfall rates (see review by Lockwood & Fröhlich 2007), they may take on additional significance.…”
Section: Direct Gcr Effectsmentioning
confidence: 99%
“…This modulation can be caused by the cosmic ray ionization, which increases the diffuse radiation, and consequently, makes the photosynthetic production more efficient (see Urban et al, 2007;Dengel et al, 2009, and references therein). Inoue et al (1979) showed that the tree growth is greater when it is not under extremely shady conditions compared to full daylight conditions.…”
Section: Solar Influencesmentioning
confidence: 99%
“…It is also possible that the correlation and the phase shift between tree-ring width and the sunspot number series can be due to the modulation of the cloudiness (Dengel et al, 2009). This modulation can be caused by the cosmic ray ionization, which increases the diffuse radiation, and consequently, makes the photosynthetic production more efficient (see Urban et al, 2007;Dengel et al, 2009, and references therein).…”
Section: Solar Influencesmentioning
confidence: 99%
“…Until eddy covariance time series are extended, it remains unclear how vegetation and climate interact to create low-frequency flux oscillations, and the relative importance of low frequency oscillations to the carbon balance of global ecosystems (Rigozo et al, 2007;Qian et al, 2008). Uncovering the mechanisms for these multi-annual energetic events require longer time series coupled with careful process-level studies (Dengel et al, 2009). …”
Section: Appendix a Modelling Low Frequency Variabilitymentioning
confidence: 99%